Praktik Konservasi Hutan Melalui Pembagian Zona Berbasis Kearifan Lokal oleh Masyarakat Adat Kampung Naga - Hikmal Muhammad Al Qisti; Eko Ribawati (Jurnal Bima : Pusat Publikasi Ilmu Pendidikan Bahasa dan Sastra, 2025)
Forests are a vital element in maintaining the balance of the ecosystem because they provide various needs for living things, such as a source of oxygen, carbon dioxide absorber, food provider, climate regulator, and biodiversity conservation place. However, along with the times, deforestation is increasingly rampant and threatens the sustainability of forest ecological functions. One potential approach to preserving forests is local wisdom-based conservation by involving indigenous communities. This study aims to analyse forest conservation practices carried out by the indigenous people of Kampung Naga in Tasikmalaya through a zone division system based on local wisdom values. Using qualitative methods and a case study approach, this research examines how the Kampung Naga community maintains ecosystem balance through structured land management and preservation of forest ecological functions. In addition, this research also explores customary values and norms that shape community behaviour in environmental management, such as the use of natural materials in house construction, sustainable management of agricultural land, and the application of silviculture principles in maintaining forest areas as a life support. The results of this study show that local wisdom can be a strong basis for sustainable natural resource management.